Beneficiation of tuba by vacuum pervaporation - Cantillan, Zenaida Reyes (2008)
Ethanol is considered as an alternative fuel to its good combustion properties but not popularly used due to its high production cost . This is the justification used in the recently approved Biofuels Act of 2006 wherein it is mandated that all fuels to be sold in the Philippines shall contain locally sourced biofuels and incentives are offered to biofuel producers. Anhydrous ethanol is the one used to be blended in gasoline but production of its through conventional distillation is energy intensive. Membrane separationprocesses in which pervaporation falls is less energy intensive and there are promising studies using pervaporation in ethanol-water mixture in other countries. Vacuum pervaporation with PTEE (Teflon) membrane was used to increase tuba's alcohol content which may be used in the study of bioethanol production in the Philippines. Temperature and vacuum pressure were varied for different treatments. Combination of three levels of temperature (60 °C, 70 °C, 80 °C) and vacuum pressure (100 mmHg, 160 mmHg, 260 mmHg) were used which resulted to nine treatments. The parameters considered were pH, total titratable acidity, specific gravity, and alcohol content in terms of percentage by volume and percentage by weight. In the nine treatments conducted, alcohol content of processed tuba by vacuum pervaporation was higher in treatment at 100 mmHg and 60 ˚C with 37% alcohol by volume, and at 100 mmHg and 70 ˚C with 36% alcohol by volume as compared with lambanog produced therough single stage distillation with 33% alcohol by volume. This study investigated the effect of pH, total titratable acidity, and specific gravity with alcohol content as affected by temperature and pressure. The pH of permeate decreases as temperature and pressure increase while alcohol content decreases. Overall, total titratable acidity and specific gravity of permeate increase as temperature and vacuum pressure increase while alcohol content decreases. The efficiency pf pervaporation in different treatments was analyzed through flux, ψ, and separation factor, a, of PTEE as affected by temperature and vacuum pressure. The flux increases as temperature and vacuum increase. The separation factor decreases as temperature and pressure increase. Further studies are recommended to find optimum pervaporator module design and operating conditions.
Thesis (M.S. Chemical Engineering)--University of the Philippines, Diliman.
Keywords: Palm wine; Pervaporation